Restoration of ankle joint, quality of life dynamics and assessment of achilles tendon rupture consequences - V.V. Vitomskyi; О.B. Lazarіeva; Ra'ad Abdul Hadi Mohammad Alalwan; M.V. Vitomskа (H.S. Skovoroda Kharkov National Pedagogical University, 2017)
Aim: to investigate the dynamics of restoration of the amplitude of motion in the ankle joint, the quality of life and to assess the effects of the breakdown of the Achilles tendon. Material: patients (n=59, of which n=30 - the main group and n=29 - the control group) were examined at 4, 8 and 16 weeks after surgery. Indicators registered with the help of: goniometry; the Achilles tendon Total Rupture Score; the scale of an assessment of consequences and results of Leppilahti implications. Results: the decrease of the total amplitude of the motion in the ankle joint takes place due to the deficiency of the amplitude of the dorsal flexion. At the end of the study the dorsal flexion rates were significantly better among the patients of main group. In particular, its deficit was 3.2 ± 1.85° in the main group and 6.8 ± 2.06° in the control group. The final total score Me (25; 75) was also better according to the questionnaire of the Achilles tendon Total Rupture Score: 82 (78; 84) points against 74 (72; 77) points (p <0.01). An assessment of consequences according to the Leppilahti score was 83.8 ± 8.58 points in the main group and 70.7 ± 10.58 points in the control group (p <0.01). Conclusions: means of physical rehabilitation help recover the amplitude of movement in the ankle joint, improve the quality of life and the effects after the rupture of the Achilles tendon. The correct methodological approach and combination of tools further improves the results.